(untitled) (Cambridge, 2002)
Contents: Introduction; The ideology of Japanese developmentalism; The managed economy; Priority production; promoting exports; High growth and liberalization; ....
Keywords: Nhật Bản,Japan; Điều kiện kinh tế,Economic conditions